Topics on Quantum Information Science (IntechOpen, 2023)
This book is devoted to current research topics in quantum information science. Chapters address issues related to the implementation of new quantum information technologies and discuss developments involving the application of information-theoretical ideas to the analysis of fundamental problems at the frontiers of contemporary physics.